Core self-evaluation and innovative behavior: mediating effect of error orientation and self-efficacy of nurses - Ma, Guiyue; Han, Zhihao; Ma, Xiaoqin (Frontiers in Psychology, 2023)
Background: Innovation plays a crucial role in advancing nursing and healthcare. Despite its significance, there is a paucity of research examining the interplay among nursing innovative behavior, core self-evaluation, error orientation, and self-efficacy. This study, grounded in Bandura's social cognitive theory, seeks to not only investigate the influence of core self-evaluation on nurses' innovative behavior but also to elucidate the mediating roles of error orientation and self-efficacy within this relationship. By addressing these dynamics, the research aims to provide a comprehensive understanding of the factors shaping nurses' innovative behaviors and contribute to the broader discourse on enhancing healthcare practices. Design: A cross-sectional study using an online questionnaire. Setting: Participants were recruited online from twenty-three hospitals in seven provinces and municipalities in China, namely Zhejiang, Anhui, Jiangxi, Guangdong, Hebei, Henan and Shanghai. Participants: A total of 741 nurses enrolled in the study. Methods: The participants completed the innovative behavior questionnaire, the core self-evaluation scale, the error orientation scale, and the self-efficacy scale online in 2023. SPSS and AMOS were used for data analysis. The reporting followed the STROBE checklist. Results: A total of 706 valid questionnaires were collected. A positive core self-evaluation was associated with more innovative behavior, and this relation was partially mediated by error orientation and self-efficacy to avoid failure. Core self-evaluation, error orientation and self-efficacy of nurses had a positive predictive effect on innovation behavior, with the path coefficients at 0.09, 0.23 and 0.39 respectively. Conclusion: Our study complements the evidence on the mechanism of action between the core self-evaluation and innovative behavior. Our findings have important clinical implications for promoting innovative behavior in nurses.